The IASP classification of chronic pain for ICD-11 - chronic cancer-related pain - Bennett, Michael I.; Kaasa, Stein; Barke, Antonia; Korwisi, Beatrice; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
AbstractWorldwide, the prevalence of cancer is rising and so too is the number of patients who survive their cancer for many years thanks to the therapeutic successes of modern oncology. One of the most frequent and disabling symptoms of cancer is pain. In addition to the pain caused by the cancer,